Foreign Direct Investment and Integration into Global Production and Distribution Networks : The Case of Poland - Kaminski, Bartlomiej; Smarzynska, Beata K. (World Bank, Washington, DC, 2014)
Not until the end of the twentieth century, the "second globalization," has the ratio of trade to Gross Domestic Product been comparable to that during the first globalization, which took place at the end of the nineteenth century and was interrupted by World War I. Technological progress has increased the importance of the international division of labor and of global production and distribution networks. Multinational corporatios have been a driving force behind these developments. As a transition economy, Poland provides an interesting case for study, as its sudden opening to foreign investment after a long period of isolation allows the process of integratio into global networks to be studies more clearly. Using Poland as a case study, the authors study multinational corporatios' role in integrating a host country into the increasingly international division of labor. They provide evidence that inflows of foreign direct investment are increasing Poland's participation in global production and distribution networks. They conclude that because of the large volume of foreign direct investment inflows expected in Poland in the near future, Poland's exports--driven by fragmented production production--will continue to expand at even faster rates than observed there recently.